Extrusion foaming behavior of a polypropylene/nanoclay microcellular foam. Issue 41 (13th July 2016) - Wang, Mingyi; Xie, Linsheng; Qian, Bo; Ma, Yulu; Zhou, Nanqiao
ABSTRACT: With maleic anhydride grafted polypropylene (PP‐ g ‐MAH) as a compatibilizer, composites of block‐copolymerized polypropylene (B‐PP)/nanoclay were prepared. The effects of the PP‐ g ‐MAH and nanoclay content on the crystallization and rheological properties of B‐PP were investigated. The microcellular foaming behavior of the B‐PP/nanoclay composite material was studied with a single‐screw extruder foaming system with supercritical (SC) carbon dioxide (CO2 ) as the foaming agent. The experimental results show that the addition of nanoclay and PP‐ g ‐MAH decreased the melt strength and complex viscosity of B‐PP. When 3 wt % SC CO2 was injected as the foaming agent for the extrusion foaming process, the introduction of nanoclay and PP‐ g ‐MAH significantly increased the expansion ratio of the obtained foamed samples as compared with that of the pure B‐PP matrix, lowered the die pressure, and increased the cell population density of the foamed samples to some extent. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44094. Abstract :